Shifting Horizons: The Impact of Constituency Statutes on Managerial Decision-Making and Operational Investments - Tanti Sugiharti; Grace Yulianti; Mohammad Chaidir (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This qualitative literature review investigates the impact of constituency statutes on managerial decision-making and operational investments in corporate governance. As organizations increasingly adopt constituency statutes, a significant shift from traditional shareholder primacy to a stakeholder-oriented approach has emerged. This review synthesizes findings from various empirical studies, highlighting how constituency statutes facilitate a broader engagement with stakeholders, thus enhancing decision-making processes and promoting sustainable operational practices. The review identifies key themes, including the improved risk management capabilities, the fostering of transparency and collaboration, and the challenges of balancing diverse stakeholder interests. It underscores the importance of aligning organizational strategies with stakeholder expectations to ensure long-term value creation and corporate resilience. Despite the positive implications, the review also acknowledges limitations, including the variability of outcomes across different sectors and the potential complexities in stakeholder engagement. This study contributes to the understanding of how constituency statutes can reshape corporate governance frameworks, emphasizing the need for ongoing research to navigate the evolving landscape of managerial decision-making.